The Effect Of Adding Metal Powders To the Spot Welded Area Of Dissimilar Metals - Mohammed, Ahmed Kadhim (Journal of natural sciences, life and applied sciences, 2017)
The process of spot welding has been and remain one of the most important manufacturing processes; the vehicle industry requires the use of this process frequently. To reduce the cost and improve the quality of the products in some applications, it was necessary to weld different metals, and due to the different specifications of welded metals it is necessary to study this situation and try to improve the specifications of the welding area. In this work, 304 stainless steels and SAE1006 was spot welded at different weld current and welding duration values because of their wide use. The aim of this research is improve the welding zone mechanical characteristics and reduce the amount of energy used by using two different types of metal powders have acceptable resistivity which added to the welding area to prevent thermal energy from dissipating rapidly allowing for a stronger bonding, This addition helped to create an extra bond between the base metal and metal powder which improved the mechanical properties of the nugget. It was found that increasing the amount of weld current and welding duration improved the mechanical features of the welding area, and from the results it was clear that the effect of the addition of titanium powder was more effective than nickel powder.